Factors contributing to housing provision in Surabaya: perspectives from real estate developers / Yosafat Raka Narendra and Prananda Navitas - Raka Narendra, Yosafat; Navitas, Prananda (Universiti Teknologi MARA, Perak, 2022)
Housing is a basic need that impacts the well-being of its inhabitants, and housing provision is key to ensuring equal access to housing. To be successful in the long term, housing provision must meet people's needs and preferences. Surabaya is the second-largest city in Indonesia and has a significant demand for housing. This article presents a part of a larger study analysing housing choice and housing preference compatibility among Millennials in Surabaya. This paper specifically aims to assess factors influencing homebuying decisions prioritised by property practitioners in Surabaya using the Analytic Hierarchy Process. Findings from this research are vital to increasing our understanding of real estate developers' priority in housing provision. Analysis reveals that location is the primary consideration for developers when engaging in real estate development activities in Surabaya. Locations near the CBD and shopping facilities are highly desirable. Before carrying out development activities, developers consider the following key variables: distance and accessibility to the central business district, shopping amenities, healthcare, and educational facilities. Other factors considered are property title and infrastructure, and amenities. Therefore, a key policy priority should be to plan for ensuring land availability for real estate development near activity centres.